Mengungkap Peran Struktur Modal Sebagai Variabel Mediasi dalam Hubungan Antara Profitabilitas Terhadap Nilai Perusahaan - Hutabarat, Febri May Windi; Gultom, Robinhot; Saragih, Rintan (Lembaga Pengembangan Kinerja Dosen, 2025)
The sampling method in this study used purposive sampling, namely companies included in the raw material sector companies (basic materials) listed on the Indonesia Stock Exchange for the 2020-2023 period that have met the criteria of 46 companies. The software analysis used is WarpPLS version 8.0. The results of this study indicate that the variables of profitability, growth opportunities, liquidity and company size directly have a positive and significant effect on company value. Capital structure has a negative and significant effect on company value. The profitability has a positive and significant effect on capital structure. The test results prove that capital structure is able to mediate the effect of profitability on company value.